Opposite acute potassium and sodium shifts during transplantation of hypothermic machine perfused donor livers. Issue 4 (4th December 2018) - Burlage, Laura C.; Hessels, Lara; van Rijn, Rianne; Matton, Alix P. M.; Fujiyoshi, Masato; van den Berg, Aad P.; Reyntjens, Koen M.E.M.; Meyer, Peter; de Boer, Marieke T.; de Kleine, Ruben H. J.; Nijsten, Maarten W.; Porte, Robert J.
Abstract : Liver transplantation is frequently associated with hyperkalemia, especially after graft reperfusion. Dual hypothermic oxygenated machine perfusion (DHOPE) reduces ischemia/reperfusion injury and improves graft function, compared to conventional static cold storage (SCS). We examined the effect of DHOPE on ex situ and in vivo shifts of potassium and sodium. Potassium and sodium shifts were derived from balance measurements in a preclinical study of livers that underwent DHOPE (n = 6) or SCS alone (n = 9), followed by ex situ normothermic reperfusion. Similar measurements were performed in a clinical study of DHOPE‐preserved livers (n = 10) and control livers that were transplanted after SCS only (n = 9). During DHOPE, preclinical and clinical livers released a mean of 17 ± 2 and 34 ± 6 mmol potassium and took up 25 ± 9 and 24 ± 14 mmol sodium, respectively. After subsequent normothermic reperfusion, DHOPE‐preserved livers took up a mean of 19 ± 3 mmol potassium, while controls released 8 ± 5 mmol potassium. During liver transplantation, blood potassium levels decreased upon reperfusion of DHOPE‐preserved livers while levels increased after reperfusion of SCS‐preserved liver, delta potassium levels were ‐0.77 ± 0.20 vs. +0.64 ± 0.37 mmol/L, respectively ( P  =   .002). While hyperkalemia is generally anticipated during transplantation of SCS‐preserved livers, reperfusion of hypothermic machine perfused livers can lead to decreased blood potassium or even hypokalemia in the recipient. Abstract : The authors examine the effect of hypothermic oxygenated machine perfusion of donor livers on ex situ and in vivo potassium and sodium shifts and find that although hyperkalemia frequently occurs after reperfusion of a conventionally preserved liver, reperfusion of a hypothermic machine‐perfused liver leads to a decrease in blood potassium or even hypokalemia in the recipient.